2014
DOI: 10.1590/0104-1169.3189.2398
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection in cervical scrapes from women attended in the Family Health Program

Abstract: Objectives to survey the prevalence of human papillomavirus, associated risk factors and genotype distribution in women who were referred to cervical cancer screening when attended in a Family Health Program. Method we conducted a cross-sectional survey, investigating 351 women. Polymerase chain reaction for DNA amplification and restriction fragment length polymorphism analysis were used to detect and typify the papillomavirus. Results virus infection was detected in 8.8% of the samples. Among the 21 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Young age is a classical independent factor associated to HPV infection and it is well reported in the scientific literature. 8 , 17 , 18 It is related to the more intense sexual activity in this age (that favors the infection) as well as to an anatomical characteristic of the young women (cervical ectopy) that exposes the columnar epithelium in the ectocervix, making it more vulnerable to pathogen infections. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young age is a classical independent factor associated to HPV infection and it is well reported in the scientific literature. 8 , 17 , 18 It is related to the more intense sexual activity in this age (that favors the infection) as well as to an anatomical characteristic of the young women (cervical ectopy) that exposes the columnar epithelium in the ectocervix, making it more vulnerable to pathogen infections. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that HPV infection was associated with multiple sexual partners 6 ; young age, more lifetime sex partners and abnormal vaginal flora 7 and non-stable sexual partners. 8 HPV persistence also presented frequencies as different as 19.2% in Porto Alegre (Rio Grande do Sul state) and 59.6% in Ouro Preto (Minas Gerais state) in two studies performed in primary public health care clinics from Brazil. 9 , 10 …”
Section: Introductionmentioning
confidence: 94%
“…Having multiple partners exposes women more to HPV infection when compared to women who had a single partner within more than one year, representing a risk factor for HPV 12 .…”
Section: Discussionmentioning
confidence: 99%
“…As there is no biological plausibility for alcoholism to be considered a protective factor for acquiring HPV infection, we believe that there may have been an information bias at the time of application of the questionnaire or perhaps alcoholism expresses another variable that was not considered in the study. Alcohol abuse was not shown to be associated with cervical infection due to HPV among HIV-positive ( Melgaço et al 2011 ) and HIV-negative women in southeastern Brazil ( Augusto et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%